Composite Index And Macroeconomic Vurnerabilities In Advanced Economies (Case Study : Indonesia) (International Journal of Psychosocial Rehabilitation, 2020)
This study examined the relation between the macroeconomic variables on the Indonesian composite index. The macroeconomic factors in Indonesia are exchange rate, GDP, inflation, and interest rates. The study used time series data from 2010–2019. 4 The results showed that the exchange rate, economic growth, inflation and interest rate did not influence the composite index but were influenced by the composition of the variable itself (composite index), which lags 1 (1⁄4 aforementioned). There are no two paths, but only one direction, from the performance of the granger causality test. Analysis based on Impulse Response (IR) shows that CI reacts to short-term and stable macroeconomic transition shocks. And the 10-quarter Variance Decompition (VD) forecast, the Composite Index ' variety, firstly with inflation, second with interest rate, third with interest rate, and fourth with economic growth.